Study on the Corrosion Kinetics of Iron in Acid and Base Medium - D. B. Patil; A. R. Sharma (E-Journal of Chemistry)
The kinetics of corrosion of iron in acid and base medium by weight loss method was investigated. The corrosion kinetics was studied in sulphuric acid, nitric acid and potassium hydroxide by weight loss method at different time intervals at 25.0 °C to 40.0 °C. The result showed that the corrosion rate vary with different time interval and different acid – base concentration. The order of corrosion of iron in these media was found to be nitric acid > sulphuric acid > potassium hydroxide. Further the specific reaction rate, half-life time, energy of activation, entropy of activation and enthalpy of activation was also evaluated.